Measuring Income Inequality Across Countries and Over Time: The Standardized World Income Inequality Database. - Solt, Frederick (Social Science Quarterly (Wiley-Blackwell), 2020)
Objective: This article documents wide‐ranging revisions to the Standardized World Income Inequality Database (SWIID), which seeks to maximize the comparability of income inequality estimates for the broadest possible coverage of countries and years. Methods: Two k‐fold cross‐validations, by observation and by country, are used to evaluate the SWIID's success in predicting the Luxembourg Income Study (LIS), recognized in the field as setting the standard for comparability. Results: The cross‐validations indicate that the new SWIID's estimates and their uncertainty are even more accurate than previous versions, extending its advantage in comparability over alternate income inequality data sets. Conclusion: Given its superior coverage and comparability, the SWIID remains the optimum source of data for broadly cross‐national research on income inequality.